HUBUNGAN KOMPENSASI DENGAN MOTIVASI KERJA - Hardiyana, Aan (Majalah Bisnis & IPTEK, 2021)
Compensation is very important for employees, because of the size of compensation would affect motivation and performance (performance) of employees. Inside there is a compensation incentive system linking compensation to performance. Compensation is also important for the organization itself, because compensation is a reflection of how the organization’s efforts to defend human resources. Motivation is one factor that determines the individual’s performance, the improved performance of the workers/ employees will improve the performance of the organization. Thus, increasing the motivation of workers /employees will improve the performance of individuals, groups, and organizations. Keywords: compensation; work motivation